Evolution of Characteristics of the Zone of Rock Loosening with Cross-Sectional Area - Jun Liu; Liwei Chen; Ning Li; Xiangjun Chen (Geofluids)
Because of the large deformation of surrounding rock mass and the different deformation characteristics of roadways with different cross-sectional areas, it is difficult to determine the means of support of roadways and the hole-sealing depth of extraction boreholes, which will cause serious roadway deformation and reduce the gas drainage rate. In order to solve these problems, this paper studies the evolution law of the zone of rock loosening around the roadway at four different cross-sectional areas (15 m2, 20 m2, 25 m2, 30 m2) by means of the acoustic field tests and numerical simulation. The results revealed three key points: first, the zone of rock loosening around the roadway is symmetrically distributed around the center of the roadway, and its shape is approximately that of a “butterfly.” Second, field tests results indicate that the rock loose zone of 1302 North floor mining roadway is in the range of 2.3–2.4 m on the side of the roadway and is 2.7–2.9 m on the central auxiliary transportation roadway. The simulation results show that the rock loose zone of 1302 North floor mining roadway is 2.5 m on the side of the roadway and is 3.0 m on the central auxiliary transportation roadway. The simulation results under four different section areas matched the field test results well, and the range of the surrounding rock loosening zone increases with the increased cross-sectional area. Third, the loose zone at the top corner and side of the roadway has a linear relationship with the cross-sectional area, and the loose zone at the bottom corner of the roadway does not change significantly with the cross-sectional area. These results have significance for determining the cross-sectional area of mine roadways in the same geological conditions, the sealing depth of the borehole, and the surrounding rock support.